FTIR imaging and ATR-FT-Far-IR synchrotron spectroscopy of pig ear skin. Issue 1 (2010) - Greve, Tanja M.; Andersen, Kristine B.; Nielsen, Ole F.; Engdahl, Anders
Abstract : FTIR imaging was performed on pig ear skin samples cryo-sectioned perpendicular to the skin surface. The OH-stretch region revealed the distribution of water; the amide II band gave the protein distribution; the C═O stretch and C–H stretch regions showed the variation in lipids. Water and proteins were similarly distributed. Triglycerides were predominantly found in the deeper skin layers whereas free fatty acids and ceramides were more dominant in the upper layers. ATR-FT-Far-IR spectroscopy with synchrotron radiation was used on full thickness pig ear skin biopsies. The Far-IR spectra showed bands in the region from 100–150 cm –1 due to hydrogen bonded proteins and a band around 180 cm –1 arising from "free" water.